Advanced fuel cell based on semiconductor perovskite La–BaZrYO3-δ as an electrolyte material operating at low temperature 550 °C. (16th October 2020) - Shah, M.A.K Yousaf; Mushtaq, Naveed; Rauf, Sajid; Akbar, Nabeela; Xing, Yueming; Wu, Yan; Wang, Baoyuan; Zhu, Bin
Abstract: As an electrolyte, enough ionic conductivity, either proton (H + ) or oxide (O 2− ) conduction, has demanded the better performance of low-temperature (especially below 550 °C) solid oxide fuel cell (LT-SOFCs). Notably, that either conductivity, higher performance, reliability, or higher cost is hampering the LT-SOFC marketing. In our current subject, we report the La-doped BZY proton conductor as an electrolyte has exhibited high ionic conductivity of 0.15 S/cm with a higher performance of 0.78 W/cm 2 at 550 °C. Also, the performance of LBZY is superior to the un-doped BZY electrolyte. Such high performance mainly ascribed due to the doping of La into BZY. Besides, the mechanism for high ion conductivity is explained. This work manifests that using the LBZY semiconductor perovskite as an electrolyte is more suitable for fuel cell technology. Graphical abstract: Image 1 Highlights: The La-doped BZY (La-BZY) perovskite was synthesized using the sol-gel method. La-BZY was applied as an electrolyte material for low-temperature solid oxide fuel cells (LT-SOFCs). The device contains (La-BZY) electrolyte has delivered the maximum power output 0.78 W/cm 2 with high OCV 1.04 V. A lower value of ohmic resistance and grain boundary resistance may provide the fast ions transport path. The La-doped BZY has verified to possess the dominant proton (H + ) conduction.